2022
DOI: 10.1038/s41598-022-16202-6
|View full text |Cite
|
Sign up to set email alerts
|

The ‘prostate-muscle index’: a simple pelvic cavity measurement predicting estimated blood loss and console time in robot-assisted radical prostatectomy

Abstract: This study was to show the impact of ‘prostate-muscle index (PMI)’, which we developed as a novel pelvic cavity measurement, in patients undergoing robot-assisted radical prostatectomy (RARP). We defined PMI as the ‘distance between the inner edge of the obturator internus muscle and the lateral edge of the prostate at the magnetic resonance imaging (MRI) slice showing the maximum width of the prostate’. Seven hundred sixty patients underwent RARP at the University of Tokyo Hospital from November 2011 to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Therefore, PMI can be used as an index to evaluate the size of the pelvic space around the prostate. 14 For the above factors that may affect the operation space, such as BMI, PV, PCI and PMI, this study was set as pelvis-prostate model BPPP. We used the AUC value of ROC curve to judge the predictive value of these four parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, PMI can be used as an index to evaluate the size of the pelvic space around the prostate. 14 For the above factors that may affect the operation space, such as BMI, PV, PCI and PMI, this study was set as pelvis-prostate model BPPP. We used the AUC value of ROC curve to judge the predictive value of these four parameters.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that PCI was positively correlated with the recovery of urinary continence 3 months after operation. Kimura et al 14 rst introduced the concept of prostate-muscle index (PMI), the anatomical structure around the prostate, which can re ect the size of the pelvic cavity around the prostate, and found that it is related to the bleeding and the operation time during RARP. The above-mentioned pelvis-prostate model (BPPP) may further increase the operation di culty of RS-RARP with narrow operation space, and further affect the goal of "three wins in a row" of radical prostatectomy (tumor control, urinary control and sexual control).…”
Section: Introductionmentioning
confidence: 99%